Critical Factors for Software Product Management: A Systematic Literature Review - Paranhos, Isadora; Santos, Gleison (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
Context: An adequate implementation of software product management brings benefits such as software quality, leadership and teamwork, control of stakeholder needs, and business objectives accountability, reducing delivery delays and improving productivity. Many organizations are unaware of the critical factors associated with software product management. Acknowledging them can assist in proactively avoiding relevant issues. Objective: We executed a systematic literature reivew to identify critical factors that can influence how software product management is executed. Results: Based on 37 studies, we identified 32 critical factors, such as strategic alignment of product management, defining the roles and activities required for software product management, Collaboration between organizational areas, definition and management of the product roadmap aligned with strategic goals, and aligning technical and architectural decisions with strategic product management. Conclusions: We present a framework organizing the factors into categories understanding the organizational context, providing the foundation for software product management, supporting effective management, and supporting product development. The identified factors can assist organizations to focus on the most relevant aspects for efficient software product management and, thus, increase the likelihood of delivering quality products, adding value to both the customer and the organization itself.